Pengaruh Kualitas Pelayanan, Harga dan Lokasi Terhadap Kepuasan Konsumen Pada Rumah Makan Wong Jowo Kalabahi di Kabupaten Alor - Mesak Yamres Awang; Theresia Lounggina Luisa Peny; Elia Maruli; Ferdinand Romelus Anigomang (Peneliti.net, 2022)
Consumer satisfaction is a person's feeling of pleasure or disappointment that arises from comparing the perceived performance of a product or result against their expectations, if the performance matches their expectations, the customer will be satisfied and will be a customer for a long time. This study aims to determine the effect of service quality, price, and location on customer satisfaction. This research was conducted at the Wong Jowo Kalabahi Restaurant, Alor Regency with a sample of 36 people. Collecting data using a questionnaire technique, interview observation, and literature study. Methods of data analysis use validity tests, reliability tests, and multiple linear regression analysis while hypothesis testing is carried out using the t-test and F-test. The results showed that partial service quality has a significant effect on customer satisfaction as indicated by the t-test significance value of 0.006. Partially, the price has a significant effect on consumer satisfaction as indicated by the t-test significance value of 0.023. Partially, location has a significant effect on consumer satisfaction as indicated by a significance value of the t-test of 0.002, and simultaneously service quality, price, and location have a significant effect on customer satisfaction as indicated by a significance value of the F test of 0.000